Getting beyond carry trade: what makes a safe haven currency? - Maurizio Michael Habib; Livio Stracca (European Central Bank (ECB), 2011)
There is already a substantial literature documenting the fact that low yield currencies typically appreciate during times of global financial stress and behave as safe havens. The main objective of this paper is to find out what the fundamentals of safe haven currencies are. We analyse a large panel of 52 currencies in advanced and emerging countries over almost 25 years of data. We find that only a few factors are robustly associated to a safe haven status, most notably the net foreign asset position, an indicator of external vulnerability, and to a lesser extent the absolute size of the stock market, an indicator of market size and development. The interest rate spread against the US is significant only for advanced countries, whose currencies are subject to carry trade. More generally, we find that it is hard to predict what currencies would do when global risk aversion is high, as estimates are imprecise and often not stable or robust. This suggests caution in over-interpreting exchange rate movements during financial crises.
Keywords: E44; F31; G15; 330; carry trade; global risk aversion; Globalisation; safe haven currencies; VIX